Critical Urban Theory versus Critical Urban Studies: A Review Debate. (September 2014) - Marcuse, Peter; Imbroscio, David; Parker, Simon; Davies, Jonathan S.; Magnusson, Warren
Abstract Critical urban theory and critical urban studies form the subject of two recent edited collections on approaches to the analysis and transformation of the contemporary capitalist city. In an exchange of commentaries by the respective editors and contributors, the introduction explains the genesis of each book and previews some of the key observations. Peter Marcuse then offers his assessment of Critical Urban Studies: New Directions, which is reciprocated by a commentary on Cities for People, Not for Profit: Critical Urban Theory and the Right to the City by Jonathan Davies, David Imbroscio and Warren Magnusson.